PENGARUH PEMBELAJARAN OPEN-ENDED DAN KONSTRUKTIVIS TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI MOTIVASI BELAJAR SISWA - Isnaeni Maryam (UM Purworejo, 2016)
The aim of this study is to determine: (1). Which one gives better mathematics learning achievement, learning with Open-ended or Constructivist, (2). Which one gives better mathematics learning achievement, high, medium or low learning motivation, (3). Which one gives better mathematics learning achievement, learning with Open-ended or Constructivist on each learning motivation of high, medium, or low category. This research is a quasi experimental study with 23 research design. The population of this research is all students on eleven grade of Senior High School. The sampling technique was conducted by stratified cluster random sampling. The samples are the students of SMA N 1 Boyolali, SMA N 3 Boyolali, and SMA N 1 Teras. The instruments which used for data collection are learning achievement tests and student learning motivation questionnaire. The data analysis technique use two-way variance of analysis with unequal cells. The conclusion of the research were drawn as follows: (1) The students with Open-ended learning have mathematics learning achievement better than Constructivist learning, (2). The students with high or medium learning motivation have mathematics learning achievement better than low learning motivation. On the other hand, high learning motivation have mathematics learning achievement better than medium learning motivation, (3). Open-ended learning provides same mathematics learning achievement with constructivist learning on high, medium and low learning motivation.